Synthesis of eupomatilone-6 and assignment of its absolute configuration - Gurjar, Mukund K.; Karumudi, Bhargava; Ramana, C. V. (Journal of Organic Chemistry, 2005)
[GRAPHICS] The Zn-mediated Barbier reaction of the biarylaldehyde 8 with crotyl bromide followed by hydroboration and oxidation provided the gamma-butyrolactones 4 and 5. The stereoselective installation of methyl group at C-3 by using LiHMDS and MeI completed the synthesis of racemic eupomatilone-6 (2) and its diastereomer 3. The spectroscopic data of 2 was in fall agreement with reported spectra of natural product, thus confirming the revised relative configuration of eupomatilone-6. Similarly, an optically active (3R,4R,5S)-isomer of eupomatilone-6 (23) was prepared in which the aldol reaction with thiazolidinethione as a chiral auxiliary was employed as a key step. On the basis of the spectroscopic data and optical rotation values of 23, the absolute configuration of eupomatilone-6 was proposed.

Synthetic studies toward macrocidins: an RCM approach for the construction of the central cyclic core - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The central macrocyclic core of the macrocidins was constructed using RCM as the key reaction. A preliminary investigation dealing with the key reactions, that is, the Dieckmann cyclization and the RCM, revealed that RCM of the beta-ketoamide is better than RCM of the corresponding acyltetramic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: acyltetramic acid; Lacey-Dieckmann cyclization; macrocidins; Ring closing metathesis

Synthesis of L-ido-configured six- and seven-membered carba-sugars - Ramana, C. V.; Chaudhuri, Siddhartha Ray; Gurjar, Mukund K. (Synthesis-Stuttgart, 2007)
Ring-closing olefin metathesis has been successfully applied to the modular construction of L-ido-configured six- and seven-membered carba-sugars.
Keywords: allylations; carbocycles; carbohydrates; Metathesis; Radical reactions

Stereoselective synthesis of beta-C-Allyl- and beta-C-propargyl-D-arabinofuranosides - Ramana, C. V.; Narute, Sachin B.; Gonnade, Rajesh G.; Patil, Rahul S. (Synthesis-Stuttgart, 2008)
The stereoselective synthesis of beta-configured C-allyl- and C-propargyl-D-arabinofuranosides (4,7-anhydro-1,2,3-deoxy-D-gluco-oct-1-enitols and -oct-1-ynitols) was addressed by employing allylation/propargylation of a dialdofuranose under aqueous Barbier reaction conditions and acid-catalyzed furan ring transposition of 5-O-mesyl-manno-oct-7-eno- or 5-O-mesyl-manno-oct-7-ynofuranoside derivatives.
Keywords: Allylation; Barbier reaction; C-glycoside; D-mannose; propargylation; Ring transposition

Small molecule inhibition of phosphatidylinositol-3,4,5-triphosphate (PIP3) binding to pleckstrin homology domains - Miao, Benchun; Skidan, Igor; Yang, Jinsheng; Lugovskoy, Alexey; Reibarkh, Mikhail; Long, Kai; Brazell, Tres; Durugkar, Kulbhushan A.; Maki, Jenny; Ramana, C. V.; Schaffhausen, Brian; Wagner, Gerhard; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The PI3-kinase (PI3K) pathway regulates many cellular processes, especially cell metabolism, cell survival, and apoptosis. Phosphatidylinositol-3,4,5-trisphosphate (PIP3), the product of PI3K activity and a key signaling molecule, acts by recruiting pleckstrin-homology (PH) domain-containing proteins to cell membranes. Here, we describe a new structural class of nonphosphoinositide small molecule antagonists (PITenins, PITs) of PIP3-PH domain interactions (IC50 ranges from 13.4 to 31 mu M in PIP3/Akt PH domain binding assay). PITs inhibit interactions of a number of PIP3-binding PH domains, including those of Akt and PDK1, without affecting several PIP2-selective PH domains. As a result, PITs suppress the PI3K-PDK1-Akt pathway and trigger metabolic stress and apoptosis. A PIT-1 analog displayed significant antitumor activity in vivo, including inhibition of tumor growth and induction of apoptosis. Overall, our studies demonstrate the feasibility of developing specific small molecule antagonists of PIP3 signaling.
Keywords: Anticancer; PIP3 antagonist

Stereospecific synthesis of C-arabinofuranosides and carba-disaccharide analogues of Motif C of cell wall AG complex of Mtb - Patil, Rahul S.; Ahire, Ketan M.; Ramana, C. V. (Tetrahedron Letters, 2012)
A simple strategy for the synthesis of alpha- and beta-C-arabinofuranosides featuring a furan ring transposition reaction has been developed. A novel double furan ring transposition reaction has proposed and executed for the synthesis of the carba-disaccharide analogue of Motif C of the cell wall AG complex of Mtb. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Arabinose; C-Glycosides; Carba-disaccharide; Cell wall AG complex; Ring transposition

Synthesis of Ag-glyconanoparticles using C-glycosides, their lectin binding studies and antibacterial activity - Ramtenki, Vilas; Raju, D.; Mehta, Urmil J.; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2013)
Two 12-C-glycosyl dodecanoic acids, namely, 1-(alpha-D-mannopyranosyl)-12-dodecanoic acid and 1-(alpha-D-glucopyranosyl)-12-dodecanoic acid were synthesized. Their ability to act as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles is displayed. These Ag C-glycosyl nanoparticles were later utilized to investigate the carbohydrate-lectin interactions. Furthermore, the specificity of mannoside binding to the surface of the Gram negative bacterium Escherichia coli has been utilized to demonstrate the enhanced antibacterial activity of Ag-C-mannosyl nanoparticles towards this bacterium as compared to Ag-C-glycosyl nanoparticles.

Synthesis of the central tricyclic core of the isatisine A: harmonious orchestration of [metal]-catalyzed reactions in a sequence - Patel, Pitambar; Reddy, B. Narendraprasad; Ramana, C. V. (Tetrahedron, 2014)
Two sequential metal-catalyzed transformations, involving [In]-catalyzed Friedel Crafts type addition of spiroaminol carbon to indole C3 followed by [Rh]-catalyzed dehydrogenative cyclization of the resulting gamma-amino alcohol culminated in the construction of the central tricyclic core isatisine A. The overall strategy employed three easily available starting compounds and delivered the complex tricyclic core in four steps with all four steps being catalytic in nature. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Dehydrogenative cyclization; Friedel-Crafts reaction; Indium chloride; Isatisine A; Rhodium; Spiro-3-indolinone

Studies toward the total synthesis of cytospolide E - Vadhadiya, Paresh M.; Rout, Jeetendra K.; Ramana, C. V. (Tetrahedron, 2015)
In this manuscript, we describe various approaches that we have examined towards the total synthesis of Cytospolide E. We initially attempted the RCM approach employing first and second generation Grubbs and Grubbs-Hoyeda catalysts resulting in the exclusive synthesis of the Z-isomer of Cytospolide E. With the Furstner catalyst, the dimerization involving the less hindered olefin was the exclusive event. Alternative approach documented is a successful cross-metathesis leading to a seco-acid with the requisite E-configuration and undesired macrodiolide formation during the attempted Shiina's lactonization. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 20-Membered macrodiolide; Nonenolide; Ring closing metathesis; Shiina lactonization; Yamaguchi esterification

Studies toward the total synthesis of parvifolals A/B: an intramolecular o-quinone methide [4 + 2]-cycloaddition to construct the central tetracyclic core - Paymode, D. J.; Ramana, C. V. (ACS Omega, 2019)
Two different approaches funded upon the intramolecular [4 + 2]-cycloaddition of in situ generated o-quinone methides have been explored to construct the central tetracyclic core of parvifolals A/B. At the outset, a cross-pinacol coupling of 2-formyl tri-O-methyl resveratrol with 4-methoxysalicylaldehyde followed by acid treatment was found to provide the desired tetracyclic core with an internal olefin. The requisite pendant aryl group has been introduced by a Pd-catalyzed direct coupling of corresponding diazonium salt.